Balanced summation model for the calculation of the fire resistance of partially encased steel sections: new proposals - Piloto, P.A.G. (2018)
Partially Encased Beams (PEB) are composite steel and concrete elements in which the web of the steel section is encased by reinforced concrete. The experimental investigation of the bending resistance was already conducted in fire and under elevated temperature (Paulo A. G. Piloto el al., 2013a) (Paulo A. G. Piloto el al., 2013b). The three-dimensional finite element solution, with precise detail of each component (steel profile, reinforcement, stirrups and concrete) was used to determine the bending resistance under three point bending configuration. Four temperature levels were tested (20, 200, 400 and 600 ºC) and three lengths were considered (2.5, 4.0 and 5.5 m), using three different cross section types, based on the dimensions of IPE100, IPE200 and IPE300 steel profiles. Two distinct types of welded stirrups were simulated (PEBA with “C” shape stirrups welded to the web and PEBB with “I” shape stirrups welded to the flange). The numerical solution method is incremental and iterative (arc length method), based on geometric and material non-linear analysis (ANSYS), using reduced integration method. Results are in accordance to the new formula presented to steel beams (P. M. M Vila Real et al., 2004) and adapted to Partially Encased Beams. The bending resistance was not significantly influenced by any type of tested welded stirrup.